Mincer's Overtaking Point and the Lifecycle Earnings Distribution - Solomon W. Polachek (Institute for the Study of Labor (IZA), 2003)
In 1958 Jacob Mincer pioneered an important approach to understand earnings distribution. In the years since Mincer?s seminal work, he as well as his students and colleagues extended the original human capital model, reaching important conclusions about a whole array of observations pertaining to human wellbeing. This line of research explained why education enhances earnings; why earnings rise at a diminishing rate throughout one?s life; why earnings growth is smaller for those anticipating intermittent labor force participation; why men earn more than women; why whites earn more than blacks; why occupational distributions differ by gender; why geographic and job mobility predominate among the young; why unemployment is lower among the skilled; and why numerous other labor market phenomena occur. This paper surveys the answers to these and other questions based on research emanating from Mincer?s original discovery. In addition, this paper provides new empirical evidence regarding Mincer?s concept of the ?overtaking age? – a topic not currently well explored in the literature. In this latter vein, the paper shows that Mincer?s original finding of a U-shaped (log) variance of earnings over the life cycle is upheld in recent data, both for the U.S. as well as at least seven other countries.
Keywords: J6; J31; J7; B31; J41; J24; D31; B20; J33; 330; human capital; earnings; overtaking age; wellbeing; Mincer; Verteilungstheorie; Arbeitsmarkttheorie; Humankapital; Lebenseinkommen; Theorie